Bilateral navicular-medial cuneiform synostosis manifesting as medial foot pain: a case report and review of the literature. Issue 2 (March 2016) - Malone, Jason B.; Raney, Ellen M.
Abstract : Isolated navicular-medial cuneiform tarsal coalition is a rare condition. Very few case reports exist, with limited treatment recommendations. We present a case of an 11-year-old with bilateral isolated osseous navicular-medial cuneiform tarsal coalition. The patient was treated with bilateral coalition excision and soft tissue interposition, with excellent results at 2 years of follow-up. The current case is unusual in being an osseous coalition rather than the more commonly seen cartilaginous or fibrous condition. In addition, this case is uncommon as being in a patient of European rather than Asian descent.